Dampak Pembelajaran PAI Berbasis Lingkungan dengan Integrasi Teknologi dan Media Sosial terhadap Karakter Religius Siswa SDN 1 Mlaran Purworejo - Arjunnajata, Rizal; Ibrahim Mamesah, Muhammad Farras Afif; Fathurrohman, Rizal (Alma Ata University Press, 2024)
Environmental Based Islamic Religious Education (PAI) holds significance not only in preserving religious values but also in emphasizing humanity’s responsibility as stewards of Earth. Environmental Challenges like pollution and globlal warming necessitate a wellprepared younger generation to serve as agents of positive change. Integrating technology and social media into PAI instruction can enchance students’ learning experiences and broaden the scope of relevant environmental messages. Additionally, fostering religious character and environmental social consciousness stands as a primary objective of this educational approach. This research aims to analyze the imppact of environmental based PAI integrated with technology and social media on the religious character and environmental awareness of 14 students at SDN 1 Mlaran. Employying a qualitative research methodology with a descriptive analytic approach, data was gathered through observation, interviews, documentation, and literature views. The findings reveal that environmental based PAI integrated with technologyy and social media positively impacts students’ religious character and environmental awareness. This positive impact manifests in heightened student awarness of the importance of environmental protection and enhanced student behaviors reflecting religious character, such as love for Allah SWT, maintaining cleanliness, and mutual assistance